Pengaruh Pelatihan Terhadap Kinerja Karyawan Departemen Human Capital dan General Service di PT Pamapersada Nusantara Site MTBU Tanjung Enim - Hirzi, Achmad Fadyan; Karimudin, Yos; Hadjri, Muhammad Ichsan (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to find out how training influences the performance of human capital and general service department employees at PT Pamapersada Nusantara Site MTBU Tanjung Enim. The population in this study amounted to 40 employees, samples were taken as many as 40 employees with non-probability sampling technique. The data analysis technique used is simple linear regression analysis. The results showed that training had a positive and significant effect on employee performance in the human capital and general service departments at PT Pamapersada Nusantara Site MTBU Tanjung Enim. Keywords: Trainning, Employee Performance